2019
DOI: 10.1111/eea.12816
|View full text |Cite
|
Sign up to set email alerts
|

Diamondback moth egg susceptibility to rainfall: effects of host plant and oviposition behavior

Abstract: Oviposition patterns of the diamondback moth (DBM), Plutella xylostella L. (Lepidoptera: Plutellidae), differ between common cabbage (Brassica oleracea L. var. capitata) and Chinese cabbage (Brassica rapa L. var. pekinensis) (Brassicaceae) host plants. This study shows that the moth prefers to oviposit on adaxial rather than abaxial leaf surfaces and petioles of both host plants. More eggs were laid in leaf veins than on leaf laminas of both host plants, especially in Chinese cabbage, where 94.6% of eggs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Such an effect was already indicated under controlled conditions (Rahman et al . 2019), and we confirmed this in the field. In addition, the larva was indirectly affected by rainfall, since sand covers basal leaves after intense rain and may cause wear on larva mandibles (Lopresti et al .…”
Section: Discussionsupporting
confidence: 82%
“…Such an effect was already indicated under controlled conditions (Rahman et al . 2019), and we confirmed this in the field. In addition, the larva was indirectly affected by rainfall, since sand covers basal leaves after intense rain and may cause wear on larva mandibles (Lopresti et al .…”
Section: Discussionsupporting
confidence: 82%
“…Wind intensity and precipitation, which differ in the localities where the experiments were conducted, were not recorded. Some studies point out that rainfall is one of the major factors causing mortality in eggs and newly hatched larvae (e.g., Caldas, 1992; Harcourt, 1966; Rahman et al., 2019). In this context, larval protection against natural enemies also prevents the larvae falling off the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, microclimate may be critical for the survival of early‐instar Lepidoptera that are small in size and limited in movement (Zalucki et al., 2002). Some studies have reported that wind and rainfall are among the major factors causing mortality in eggs (Kyi et al., 1991; Rahman et al., 2019) and newly hatched larvae (Caldas, 1992; Harcourt, 1966; Kyi et al., 1991), and light intensity can affect larval performance through its effects on the primary and secondary metabolism of host plants (Manuwoto & Scriber, 1985). Therefore, in field conditions a combination of factors may affect the interaction between herbivores and their host plants.…”
Section: Introductionmentioning
confidence: 99%
“…The diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae) is one of the most serious pests of cruciferous vegetables, and among the most widely distributed. of all lepidopterans worldwide (Odhiambo et al, 2010;Silva & Furlong, 2012;Wei et al, 2013;Fu et al, 2014;Ahmad et al, 2018;Rahman et al, 2019). High pest densities in crops result mainly from insecticide resistance (Liu et al, 1981(Liu et al, , 1982Hama, 1987;Adachi & Fujitomi, 1995;Odhiambo et al, 2010;Li et al, 2016) and pest resurgence due.…”
Section: Introductionmentioning
confidence: 99%